(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The development of the moth ldaea inquinata (Scop.) on 20 medicinal plants and on 13 foodstuffs was tested at 26±1°C and 70±5% r.h.. The insect was not able to complete its development on: Camellia sinensis and Vitis vinifera leaves, whole Illicium verum fruits, Cinnamomum zeylanicum bark, pieces of Quassia amara wood, whole capsules of Vanilla planifolia, and Zingiber officinale rhizomes, soft-wheat flour, hazel-nut flour, almond flour, raisins and cocoa powder. As far as medicinal plants, the highest number of adults was found on whole fruits of Foeniculum vulgare, and the highest susceptibility indexes were recorded on Angelica archangelica roots and on Crataegus monogyna flower heads respectively. The highest mean number of adults was recorded on bran (≥20 mesh), with a mean developmental period of 62 days. The highest susceptibility indexes were recorded on bran and maize meal. The shortest mean developmental period was observed on wheat germ (58.5±0.96).